(3TQM eaJGM GdYdhes - (3eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj, SYO GdOjf , J (B793 (3g` s; (3GdScGcj , SQGL GdOjf CHh jYbhH jhSa Hf CHj HcQ Hf eMeO Hf Ydj GdScGcj GdNhGQRej GdMfaj, GdScGcj,J (B626 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje NHQ eMeO jhTM Hg UOQ GdcdGe MeO Gddg GdPi Ndb GdEfSGf hYdeg GdHjGf CJe dg GdEMSGf aCdgeg GdHjGf LYd ajg GdaUGMI eaJGMkG daJM HGH GdfLGM s
(3BNQgG (B:s
(3Ci HcdeI Yde GdeYGfi hGdHjGf HYde GdESJOdGd hdg GdMeO Ydi cd MGd JeJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B222 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B282s
Keywords: (3GdeYGQa GdYGeIs